Maternal Employment and Childcare Arrangements in Indonesia: The Needs for Childcare Support Policies - Michelle Andrina (Masyarakat Indonesia, 2022)
Women need childcare supports to maximize their potential to contribute to their economy. This article aims to investigate childcare arrangement practices among families whose working mothers and identify the necessities to support them in their work lives. This study employs explanatory sequential mixed methodsQuantitative data were collected from Indonesia's Socio-Cultural and Education Module of the 2018 National Socio-Economic Survey. Qualitative data resulted from interviews with working mothers are applied as complementary for the quantitative findings to result contextual understandings concerning necessary supports from the government. Findings show that most families rely on grandparents to supervise the toddlers, while some others trust the older siblings, who possibly not be matured yet. Working mothers require affordable daycare as a safe place for their children as well as to ease their families’ burdens.  As more women become parts of the workforce, it is crucial for the government to provide inexpensive public daycares, especially for families with limited resources. In addition, the government should promote the provision of lactation rooms and child-friendly spaces, launch social media campaigns, and conduct community events to educate society concerning children's rights and safety, equal responsibilities between men and women, and accommodative working arrangements.